Examples
2(x2−1)=16 , (0,4)
Step 1
Step 1.1
Divide each term in 2(x2−1)=16 by 2.
2(x2−1)2=162
Step 1.2
Simplify the left side.
Step 1.2.1
Cancel the common factor of 2.
Step 1.2.1.1
Cancel the common factor.
2(x2−1)2=162
Step 1.2.1.2
Divide x2−1 by 1.
x2−1=162
x2−1=162
x2−1=162
Step 1.3
Simplify the right side.
Step 1.3.1
Divide 16 by 2.
x2−1=8
x2−1=8
x2−1=8
Step 2
Step 2.1
Add 1 to both sides of the equation.
x2=8+1
Step 2.2
Add 8 and 1.
x2=9
x2=9
Step 3
Take the specified root of both sides of the equation to eliminate the exponent on the left side.
x=±√9
Step 4
Step 4.1
Rewrite 9 as 32.
x=±√32
Step 4.2
Pull terms out from under the radical, assuming positive real numbers.
x=±3
x=±3
Step 5
Step 5.1
First, use the positive value of the ± to find the first solution.
x=3
Step 5.2
Next, use the negative value of the ± to find the second solution.
x=−3
Step 5.3
The complete solution is the result of both the positive and negative portions of the solution.
x=3,−3
x=3,−3
Step 6
Step 6.1
The interval (0,4) does not contain −3. It is not part of the final solution.
−3 is not on the interval
Step 6.2
The interval (0,4) contains 3.
x=3
x=3